2012
DOI: 10.1073/pnas.1206820109
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cannabis users show neuropsychological decline from childhood to midlife

Abstract: Recent reports show that fewer adolescents believe that regular cannabis use is harmful to health. Concomitantly, adolescents are initiating cannabis use at younger ages, and more adolescents are using cannabis on a daily basis. The purpose of the present study was to test the association between persistent cannabis use and neuropsychological decline and determine whether decline is concentrated among adolescent-onset cannabis users. Participants were members of the Dunedin Study, a prospective study of a birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
887
13
35

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,250 publications
(968 citation statements)
references
References 51 publications
33
887
13
35
Order By: Relevance
“…None of these variables were found to have a significant association with either IQ or premorbid IQ among cases or controls (all p N .05). We only found that controls who had smoked cannabis after age 16, had higher IQ than controls that had smoked cannabis earlier in life (p = .016) (see also Meier et al, 2012) (Table 3). There was also a significant main effect of cannabis use (F(1,222) = 8.1, p = .005, η 2 = 0.036).…”
Section: Patterns Of Cannabis Use and Iqmentioning
confidence: 73%
See 1 more Smart Citation
“…None of these variables were found to have a significant association with either IQ or premorbid IQ among cases or controls (all p N .05). We only found that controls who had smoked cannabis after age 16, had higher IQ than controls that had smoked cannabis earlier in life (p = .016) (see also Meier et al, 2012) (Table 3). There was also a significant main effect of cannabis use (F(1,222) = 8.1, p = .005, η 2 = 0.036).…”
Section: Patterns Of Cannabis Use and Iqmentioning
confidence: 73%
“…This is unexpected as it has been shown that cannabis use can impair cognition in healthy subjects (Fried et al, 2005;Meier et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Long-term cognitive impairments and elevated risk of psychiatric disorders in regular marijuana users are less pronounced when use is initiated in adulthood, instead of in adolescence (Arsenault et al, 2004;Meier et al, 2012). Our hypothesis predicts that the long-term effects of WIN on cortical oscillations would be restricted to adolescent exposure.…”
Section: Adolescent But Not Adult Win Administration Suppresses In mentioning
confidence: 93%
“…Persistent marijuana use before adulthood may permanently impair cognitive functioning (Solowij et al, 2002;Meier et al, 2012) and confer a higher risk of developing psychiatric diseases, such as schizophrenia, in susceptible individuals (Arseneault et al, 2004). Chronic adolescent, but not adult, cannabinoid exposure produces lasting working memory impairments and recapitulates other schizophrenia endophenotypes in rodents, including impaired sensorimotor gating, social avoidance, and anhedonia/avolition (Schneider and Koch, 2003;O'Shea et al, 2004;Quinn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Smoked marijuana may also adversely affect pulmonary function and immune modulation, leading to increased risk of pulmonary infections [10]. Chronic use of cannabis may be associated with persistent cognitive delays [11]. Long-term cannabis use is thought to produce irreversible impairment in memory, attention, and the organization and integration of complex functions [12].…”
Section: Introductionmentioning
confidence: 99%